Formulation of O/W Emulsions containing Rice Bran Oil from Various production methods and Evaluation of free radical Scavenging activity - Rattanachot Mongkollikit (Chulalongkorn University, 2014)
Thesis (M.Sc. in Pharm)--Chulalongkorn University, 2007